Sistem Informasi Administrasi pada Puskesmas Kaliwungu Kudus Berbasis Web dan Email Notifikasi - Khoiruz Zahro; Muhammad Arifin; Wiwit Agus Triyanto (Journal of Software Engineering Ampera, 2021)
In managing data at the Kaliwungu Kudus Public Health Center such as patients, medical records, drug data, they still use desktop and excel-based applications so that when the computer experiences technical problems it will be prone to data loss, and when the puskesmas will hold mobile activities to the village, residents usually have to wait for information from the community. village head or other apparatus so that it will increase the time in notification of information. The purpose of this research is to create an administrative system that can help collect patient data, medical recaps, drug data via the web and because this is web-based, there is no need to worry about computer problems and also notifications via email notifications so that residents who are registered at the Puskesmas will get information about activities that will be carried out by the puskesmas more quickly. With this system, it is hoped that it will make data collection at the Kaliwungu Kudus Health Center easier and also help the villagers to get information more quickly about the activities that will be carried out by the Kaliwungu Kudus Community Health Center.